APPLICATION OF ORGANIC CULTIVATION TO MAINTAIN THE HARMONY OF NATURE AND FOOD SAFETY - Laela, Fadhilatul; Judhaswati, Ratna Dewi (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Modernization has an impact on increasing public literacy about the importance of food products that are safer for health. In addition, the society has also been aware of the dangers of pesticides and other chemical products used in agricultural businesses that can pollute the environment and disturb the balance of nature. Writing this review aims to describe the positive impact of organic farming on natural balance and food security and to formulate policy recommendations that can be made to expand the range of application of organic farming methods. From the various journals that have been reviewed, the results show that organic farming requires lower inputs and energy than conventional farming. In addition, the diversity of organisms in organic cultivation systems is also more abundant, so that the impact will be more positive for maintaining the balance of nature. The application of organic cultivation systems has also been proven to produce food products that are safer for consumption and more economically profitable for farmers. Therefore, efforts to implement an organic crop cultivation system are important to be carried out with the support of all component of society.